2017
DOI: 10.1097/shk.0000000000000851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Levosimendan on Cellular Metabolic Alterations in Patients With Septic Shock

Abstract: Introduction:Mitochondrial dysfunction and consequent cellular energetic failure play a key role in the development of sepsis-related organs failure. Evidence suggests that the pleiotropic effects of levosimendan may positively affect cellular metabolism during septic shock.Objectives:To investigate changes in the concentration of glucose, lactate, pyruvate, and glycerol in the extracellular fluid of the skeletal muscle following levosimendan administration in patients with septic shock.Methods:The study was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…[ 2 , 31 ] As there is no proven treatment for SIMD, further study is needed to investigate the efficacy of levosimendan or mechanical support with extracorporeal membrane oxygenation. [ 32 ] A meta-analysis reported that levosimendan reduced mortality compared to standard inotropic therapy possibly because it does not stimulate β-adrenergic receptor. [ 33 ] In SICMP, supportive care is a crucial strategy during the acute phase.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 , 31 ] As there is no proven treatment for SIMD, further study is needed to investigate the efficacy of levosimendan or mechanical support with extracorporeal membrane oxygenation. [ 32 ] A meta-analysis reported that levosimendan reduced mortality compared to standard inotropic therapy possibly because it does not stimulate β-adrenergic receptor. [ 33 ] In SICMP, supportive care is a crucial strategy during the acute phase.…”
Section: Discussionmentioning
confidence: 99%
“…Levosimendan is a calcium-sensitising drug that has multiple effects aside from positive inotropy, which are potentially beneficial in sepsis. For example, in a recent pilot randomised controlled trial in 20 patients, levosimendan lowered the lactate/pyruvate ratio, which suggests beneficial effect on cellular metabolic alterations in septic shock (42). However, a large superiority trial that tested the hypothesis that levosimendan would reduce the severity of organ dysfunction in adults with sepsis, in 516 adult patients with sepsis, levosimendan compared to placebo was not associated with less severe organ dysfunction or lower mortality.…”
Section: Vasopressors and Inotropic Agentsmentioning
confidence: 99%
“…In an updated meta‐analysis comprising five trials,20, 21, 22, 23, 24 we found no statistically significant difference in short‐term mortality in patients with septic shock treated with dobutamine vs. levosimendan (Fig. 2, Fig.…”
Section: Resultsmentioning
confidence: 92%